2023
DOI: 10.1111/aogs.14613
|View full text |Cite
|
Sign up to set email alerts
|

Optical genome mapping for detection of chromosomal aberrations in prenatal diagnosis

Abstract: Introduction: Chromosomal aberrations are the most important etiological factors for birth defects. Optical genome mapping is a novel cytogenetic tool for detecting a broad range of chromosomal aberrations in a single assay, but relevant clinical feasibility studies of optical genome mapping in prenatal diagnosis are limited. Material and methods: We retrospectively performed optical genome mapping analysis of amniotic fluid samples from 34 fetuses with various clinical indications and chromosomal aberrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…OGM is an emerging and promising cytogenomic technology that has the potential to detect major classes of SVs [3]. Combining microfluidics, automated image analysis and high-resolution microscopy, OGM allows us to detect insertions and deletions above 500 bp in length and other SVs above 30 kbp in length [4]. There are two distinct algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…OGM is an emerging and promising cytogenomic technology that has the potential to detect major classes of SVs [3]. Combining microfluidics, automated image analysis and high-resolution microscopy, OGM allows us to detect insertions and deletions above 500 bp in length and other SVs above 30 kbp in length [4]. There are two distinct algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 A growing number of studies have recently demonstrated the efficiency and superiority of OGM in various clinical settings, including both prenatal and postnatal congenital conditions, as well as various hematological and other malignancies. [5][6][7] Here, we explore the value of OGM in identifying cryptic BCRs using a case series from our clinical practice. This study was approved by the ethics committee of the Nanjing Drum Tower Hospital affiliated with Nanjing University Medical School (no.…”
mentioning
confidence: 99%
“…Optical genome mapping (OGM), an emerging technology from Bionano Genomics, has a high resolution for detecting nearly all types of genomic SVs and has been recognized as a revolution in next-generation cytogenomic analysis 3,4 . A growing number of studies have recently demonstrated the efficiency and superiority of OGM in various clinical settings, including both prenatal and postnatal congenital conditions, as well as various hematological and other malignancies 5–7 . Here, we explore the value of OGM in identifying cryptic BCRs using a case series from our clinical practice.…”
mentioning
confidence: 99%
“…A genome map is constructed based on the labeling pattern of each strand, and pattern differences detected by comparison with reference data can reveal SVs and large-scale tandem repeat arrays. Studies have applied OGM to diagnose hematologic malignancies [ 3 - 6 ], solid tumors [ 7 , 8 ], and constitutional genetic disorders [ 9 - 12 ].…”
mentioning
confidence: 99%